Моделирование поведения лица принимающего решения на виртуальном предприятии. Применение моделей в информационных технологиях - Собчак, Андрей Павлович; Попова, Ольга Игоревна (НТУ "ХПИ", 2016)
Проведен анализ математических моделей, описывающих поведение руководителя виртуального предприятия. Освещены проблемы создания искусственного интеллекта, как совокупности средств программного обеспечения, которые по своему принципу действия сходны с интеллектом человека и существенно облегчают его умственный труд, помогают в решении задач и расширяют границы познания окружающего мира и определения, что необходимо предпринять для того, чтобы принцип действия и оперативности искусственного интеллекта был максимально приближен к человеческому мозгу. При этом установлена связь искусственного и естественного интеллекта.

The analysis of mathematical models describing the behavior of the head. Efforts in torture comprehension problems of artificial intelligence, as a set of software tools, which by their principle of operation similar to the intelligence of man and essentially facilitate his intellectual work, help in solving various kinds of problems and extend the boundaries of knowledge of the world and determine that need to be taken to ensure that the principle of action and efficiency of artificial intelligence as close as possible to the human brain. It was revealed to more deeply understand and appreciate the natural intelligence which man possesses, and to develop a model of their own actions at a certain level. The connection of artificial and natural intelligence, the advantages and disadvantages of each of them identified. Consideration of how to implement the knowledge in using artificial intelligence system "artificial and natural intelligence". The necessity of taking into account the limitations in the construction of systems with artificial intelligence and setting behavior analyzer according to the type of human nature. It proposed a comprehensive understanding of the human brain as a complex, evolving, dynamic, procedural system, and the principles of mapping and processing of information received by a person from the surrounding reality. The practical significance of the study is to establish the need to address restrictions on the construction of systems with artificial intelligence and setting behavior analyzer according to the type of human nature.
Modeling the behavior of decision makers in the virtual enterprise. Application of models in information technology
Keywords: моделирование; виртуальное предприятие; принятие решения; искусственный интеллект; информационные технологии; modeling; virtual enterprise; decision maker; artificial intelligence; information technology